Community pharmacists' perspectives towards automated pharmacy systems and extended community pharmacy services: An online cross-sectional study - Khalid S. Alghamdi; Max Petzold; Mahdi H. Alsugoor; Hafiz A. Makeen; Kudaisi H. Al Monif; Laith Hussain-Alkhateeb (Elsevier, 2023)
Background: Private sector partnerships through community pharmacies are essential for effective healthcare integration to achieve the United Nations 2030 Agenda for Sustainable Development Goals. This partnership can provide significant clinical outcomes and reduce health system expenditures by delivering services focused on patient-centred care, such as public health screening and medication therapy management. Objectives: To assess the understanding of the proposed strategic and health system reform in Saudi Arabia by exploring community pharmacists' perspectives towards the capacity and readiness of community pharmacies to use automated pharmacy systems, provide extended community pharmacy services, and identify perceived barriers. Materials and methods: This multicentre, cross-sectional, web-based survey was conducted in Saudi Arabia (October-December 2021). Graphical and numerical statistics were used to describe key dimensions by the background and characteristics of the respondents, and multiple ordinal logistic regression analyses were sought to assess their associations. Results: Of the 403 consenting and participating community pharmacists, most were male (94%), belonged to chain pharmacies (77%), and worked >48 h per week (72%). Automated pharmacy systems, such as electronic prescriptions, were never utilised (50%), and health screening services, such as blood glucose (76%) and blood pressure measurement (74%), were never provided. Services for medication therapy management were somewhat limited. Age groups ≤40 years, chain pharmacies, >10 years of experience and ≥ 3 pharmacists in place with <100 daily medication prescriptions and Jazan province were significantly more likely to provide all medication therapy management services than others. Operational factors were the barriers most significantly associated with the independent variables. Conclusion: The results showed that most services and automated pharmacy systems remained limited and well-needed. When attempting to implement these services to drive change, community pharmacies face numerous challenges, and urgent efforts by private and government sectors are essential to improve pharmaceutical care in community pharmacy settings.